1999
DOI: 10.1007/s007010050350
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain Therapy After Lumbar Disc Surgery

Abstract: The results suggest that the application of tramadol and diclofenac during the first 48 hours after lumbar microdiscectomy results in a reduction in postoperative pain without complications. We suggest that the use of this combination can be a beneficial adjunct to lumbar disc surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Opioid analgesics are the traditional first-line medication in this setting but may induce unwanted side effects, such as nausea and vomiting, sedation, and respiratory depression. Several studies have shown that non-opioid analgesics provide effective pain relief in patients with acute postoperative pain after lumbar disk surgery, either as a substitute for or as an adjunct to opioid analgesia (4,7,8). However, this is the first prospective, randomized, double-blind, placebo-controlled study that compares IV administered parecoxib, paracetamol, and metamizol for pain relief in the early postoperative period after lumbar disk surgery.…”
Section: Discussionmentioning
confidence: 94%
“…Opioid analgesics are the traditional first-line medication in this setting but may induce unwanted side effects, such as nausea and vomiting, sedation, and respiratory depression. Several studies have shown that non-opioid analgesics provide effective pain relief in patients with acute postoperative pain after lumbar disk surgery, either as a substitute for or as an adjunct to opioid analgesia (4,7,8). However, this is the first prospective, randomized, double-blind, placebo-controlled study that compares IV administered parecoxib, paracetamol, and metamizol for pain relief in the early postoperative period after lumbar disk surgery.…”
Section: Discussionmentioning
confidence: 94%
“…Of these, 6 studies were excluded. Three studies compared NSAIDs with other active treatment, 9,45,51 duplicated data were presented in 1, 42 outcomes of interest could not be obtained in 1, 43 and the surgery was performed to treat scoliosis in adolescents in 1. 30 Therefore, 17 studies composed of 789 adult patients were included ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This time point was used for further subgroup and sensitivity analyses. The majority of authors reported pain intensity results over the following intervals: 0-2 hours (8 studies 1,3,17,21,37,41,49,50 ), 4-6 hours (11 studies, 1,9,21,31,35,[37][38][39][40]41 ), 24 hours (14 studies 1,11,21,23,27,31,35,[37][38][39][40]41,50 ), 48 hours (5 studies 11,21,27,31,35 ), and 72 hours (2 studies 27,35 ). Opioid consumption results were reported over the following intervals: 0-2 hours (8 studies 1,3,17,21,37,41,49,50 ), 4-6 hours (6 studies 11,[37][38]…”
Section: Resultsmentioning
confidence: 99%